ENGLISH INSTRUCTION FOR EARLY-CHILDHOOD EDUCATION (A CASE STUDY AT TK RIYADUL JANNAH SIMO BOYOLALI CENTRAL JAVA YEAR 2016) - Win Listyaningrum Arifin (Englisia: Journal of Language, Education, and Humanities, 2016)
Kindergarten children are creative, resourceful, and imaginative. During the kindergarten years, the children’s perceptual skills can be sharpened by encouraging them to observe specific aspects of their environment. In line with the need of English as the international and the most spoken language, English subject is being taught to students from elementary to university level, or even to kindergarten. The consideration is that English should be taught very early as the students will easily absorb the English materials later on. However, kindergarten teachers in Indonesia are actually not the experts of the field. There are still limited graduated teachers majoring in kindergarten or early childhood education department. Promoting an effective learning can only be well done by teachers who are qualified enough. In addition, there is no best method in teaching such a foreign language to these young students. To sum up, teaching a foreign language to very young students who are living in and accustomed to the first language is a challenging task for the kindergarten teachers.